2019
DOI: 10.1039/c9bm01072f
|View full text |Cite
|
Sign up to set email alerts
|

Engineering natural matrices with black phosphorus nanosheets to generate multi-functional therapeutic nanocomposite hydrogels

Abstract: Natural matrices are engineered with black phosphorus nanosheets to generate therapeutic nanocomposite hydrogels with promising multi-functions, providing a facile and efficient therapeutic strategy for bone tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 50 publications
3
56
0
Order By: Relevance
“…The d-spacing of lattice fringes in BPNSs and BP@BMP 2 nanosheets photographed by HR-TEM was 0.28 and 0.25 nm respectively ( Figure 1E,G), as expected in a typical BPNS structure. [29,[34][35][36] XPS (Kratos, AXIS Ultra DLD) results demonstrated that the P2p and P2s peaks of BPNSs located at about 130 and 200 eV, consisting with the standard peak reported by previous study, which confirmed the successful preparation of BPNSs. [33] Furthermore, BP@BMP 2 nanosheets exhibited high carbon, oxygen, and nitrogen concentration and the standard P2p and P2s peaks, which demonstrated that the successful modification of BMP 2 ( Figure 1H; Figure S2, Supporting Information).…”
Section: Characterization Of Bp@bmp 2 Nanosheetssupporting
confidence: 79%
“…The d-spacing of lattice fringes in BPNSs and BP@BMP 2 nanosheets photographed by HR-TEM was 0.28 and 0.25 nm respectively ( Figure 1E,G), as expected in a typical BPNS structure. [29,[34][35][36] XPS (Kratos, AXIS Ultra DLD) results demonstrated that the P2p and P2s peaks of BPNSs located at about 130 and 200 eV, consisting with the standard peak reported by previous study, which confirmed the successful preparation of BPNSs. [33] Furthermore, BP@BMP 2 nanosheets exhibited high carbon, oxygen, and nitrogen concentration and the standard P2p and P2s peaks, which demonstrated that the successful modification of BMP 2 ( Figure 1H; Figure S2, Supporting Information).…”
Section: Characterization Of Bp@bmp 2 Nanosheetssupporting
confidence: 79%
“…RNA sequencing analysis demonstrated that the Wnt signaling pathway was involved in in situ bone regeneration. Moreover, a new class of 2D BP nanosheets have been employed as photothermal agents for the remote control of bone regeneration 106 , 107 . These BP nanosheets could upregulate the expression of heat shock proteins in human BMSCs and thus enhance bone tissue regeneration by remote control of NIR light irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…115 To simultaneously combat infection and improve bone regeneration, a multi-functional, therapeutic, BP-based hydrogel nanocomposite was designed. 116 Upon NIR irradiation, the nanocomposite hydrogel demonstrated efficient photothermal antibacterial features ( Figure 6A and B). What's more, this nanocomposite hydrogel can promote osteogenesis in the absence of osteoinductive factors in vitro, and in the meantime induce newborn cranial bone tissue formation ( Figure 6C).…”
Section: -mentioning
confidence: 99%